Biscuit Contaminants, Their Sources and Mitigation Strategies: A Review - Antonella Pasqualone (MDPI AG, 2021)
The scientific literature is rich in investigations on the presence of various contaminants in biscuits, and of articles aimed at proposing innovative solutions for their control and prevention. However, the relevant information remains fragmented. Therefore, the objective of this work was to review the current state of the scientific literature on the possible contaminants of biscuits, considering physical, chemical, and biological hazards, and making a critical analysis of the solutions to reduce such contaminations. The raw materials are primary contributors of a wide series of contaminants. The successive processing steps and machinery must be monitored as well, because if they cannot improve the initial safety condition, they could worsen it. The most effective mitigation strategies involve product reformulation, and the use of alternative baking technologies to minimize the thermal load. Low oxygen permeable packaging materials (avoiding direct contact with recycled ones), and reformulation are effective for limiting the increase of contaminations during biscuit storage. Continuous monitoring of raw materials, intermediates, finished products, and processing conditions are therefore essential not only to meet current regulatory restrictions but also to achieve the aim of banning dietary contaminants and coping with related diseases.